KARAKTERISTIK FISIKO-KIMIA, MIKROBIOLOGIS, DAN SENSORIS DENDENG GILING DAGING KERBAU DAN SAPI DENGAN PENGERINGAN SINAR MATAHARI DAN OVEN - , BASTONI; , Dr. Ir. Setiyono, SU ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research was aimed to determine and to compare the physical - chemical , microbiological and sensory characteristics of beef and buffalo jerky dried by sun drying and oven drying methods. This research used two treatment of dried beef and buffalo meat jerky (sun drying and oven drying methods). Each treatment consisted of three replication. Sun drying was did during 7 hours per day in 3 days, while oven drying was did during 15 hours at temperature of 50oC . The collected data were analyzed using Randomized Complete Block Design and the difference was tested by factorial method (2x2). The for analysys was software Statistical Package for the Social Sciences (SPSS). Ground beef jerky research results that show significantly different (P<0.05) in terms of drying methods on physico-chemical characteristics (pH, tenderness, fat content and protein content) and sensory (color). Judging from the type of meat physico-chemical characteristics (levels of protein and ash content) and sensory (color, texture, and tenderness). Judging from the interaction between the method of drying the meat is kind of physico-chemical characteristics (protein content) and sensory (color and texture), while the test results showed no significant difference (P>0.05) was observed from drying methods physico-chemical characteristics (ash content, water content, and water activity), microbiological (total plate count) and sensory (taste, aroma , texture, tenderness and acceptance). Judging from the type of meat physico-chemical characteristics (tenderness, fat content, water content, and water activity), microbiological (total plate count) and sensory (taste, aroma, and acceptance). Judging from the interaction between the different types of meat drying method is physico-chemical characteristics (pH, tenderness, water content, ash content, fat content, and water activity), microbiological (total plate count), and sensory (taste, aroma, tenderness and acceptance).